Understanding the Microstructure Formation of Polymer Films by Spontaneous Solution Spreading Coating with a High‐Throughput Engineering Platform. Issue 17 (8th July 2021) - Wang, Rong; Lüer, Larry; Langner, Stefan; Heumueller, Thomas; Forberich, Karen; Zhang, Heyi; Hauch, Jens; Li, Ning; Brabec, Christoph J.
Abstract: An important step of the great achievement of organic solar cells in power conversion efficiency is the development of low‐band gap polymer donors, PBDB−T derivatives, which present interesting aggregation effects dominating the device performance. The aggregation of polymers can be manipulated by a series of variables from a materials design and processing conditions perspective; however, optimization of film quality is a time‐ and energy‐consuming work. Here, we introduce a robot‐based high‐throughput platform (HTP) that is offering automated film preparation and optical spectroscopy thin‐film characterization in combination with an analysis algorithm. PM6 films are prepared by the so‐called spontaneous film spreading (SFS) process, where a polymer solution is coated on a water surface. Automated acquisition of UV/Vis and photoluminescence (PL) spectra and automated extraction of morphological features is coupled to Gaussian Process Regression to exploit available experimental evidence for morphology optimization but also for hypothesis formulation and testing with respect to the underlying physical principles. The integrated spectral modeling workflow yields quantitative microstructure information by distinguishing amorphous from ordered phases and assesses the extension of amorphous versus the ordered domains. This research provides an easy to use methodology to analyze the exciton coherence length in conjugated semiconductors and will allow to optimize exciton splitting in thin film organic semiconductor layers as a function of processing. Abstract : A machinery of information : A high‐throughput platform (HTP) is developed for automated preparation and characterization of polymer films by spontaneous film spreading coating. In combination with Gaussian Process Regression, the microstructure information of polymer films can be successfully predicted, which provides us the possibility to accelerate the decipherment of process−structure−property relationships for functional polymer films.